2008
DOI: 10.1007/s00105-008-1636-6
|View full text |Cite
|
Sign up to set email alerts
|

Exsudatmanagementkapazität moderner Wundauflagen für die Therapie des Ulcus cruris venosum unter Kompressionstherapie

Abstract: Major components in the conservative treatment of patients with chronic venous leg ulcers are compression therapy and modern wound dressings. Both therapies are used simultaneously. Consequently it is important to know the exudate capacity of modern wound dressings changes during compression therapy. In the first part of our study we analyzed the maximum exudate capacity of 15 modern wound dressings. In the second part we showed that under compression stockings of class 2, a reduction of 44.08% and under compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…There exists no perfect wound dressing for every kind of wound or every phase of wound healing 9–11 . One aspect is the patient’s individual life situation, which should be considered when choosing an individual‐adapted therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There exists no perfect wound dressing for every kind of wound or every phase of wound healing 9–11 . One aspect is the patient’s individual life situation, which should be considered when choosing an individual‐adapted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There exists no perfect wound dressing for every kind of wound or every phase of wound healing. [9][10][11] One aspect is the patient's individual life situation, which should be considered when choosing an individual-adapted therapy. For example, patients, who are unable to change their dressings for several days, should have dressings with stronger adhesion properties.…”
Section: Discussionmentioning
confidence: 99%
“…Within the context of a complex treatment strategy of patients with chronic wounds targeted at the cause, the use of modern wound dressings is sensible, for example, to realize a moist wound environment with exudate management. It is suggested that in therapy‐refractory cases selection of a wound dressing might potentially achieve renewed induction of stagnant wound healing [8]. Studies to date indicate that Tegaderm™ Matrix can have a positive effect on previously stagnant wound healing [9].…”
Section: Discussionmentioning
confidence: 99%